1964
DOI: 10.1007/bf03002131
|View full text |Cite
|
Sign up to set email alerts
|

Innovan-N2O anaesthesia in normal men effect on respiration, circulatory dynamics, liver function, metabolic functions, acid-base balance, and psychic responses

Abstract: MUN)3ELEER AND DECASTRO reduced an analgesic a~d sedatwe state for surgmal procedures, without using balblturates or volatile a~aesthetm agents, whmh they called neuroleptanalgesla They employed a comb!#atlon of drugs developed by Janssen m Belgmm to* aecomphsh this state and many anaesthetists are now usmg thas techmque m Europe 1-~ Of the numerous new analgesm and sedatwe ~lrugs recently developed by Janssen, the combination of droperldol (R4749, dehydrobenzpendol, Inapsine| and fentanyl (R4263, phentanyl, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
4

Year Published

1965
1965
1977
1977

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 26 publications
1
5
0
4
Order By: Relevance
“…This state of "inner anxiety" is more likely to occur when dehydrobenzperidol alone is given. The marked anti-emetic effect of dehydrobenzperidol on experimental animals and on man has been described in earlier studies (DOBKIN et al 1964…”
Section: Dehydrobenzperidolsupporting
confidence: 55%
See 3 more Smart Citations
“…This state of "inner anxiety" is more likely to occur when dehydrobenzperidol alone is given. The marked anti-emetic effect of dehydrobenzperidol on experimental animals and on man has been described in earlier studies (DOBKIN et al 1964…”
Section: Dehydrobenzperidolsupporting
confidence: 55%
“…These ciharacteristics make it easy to regulate the level of fentanyl analgesia, which approaches the good controllability of inhalation anesthetics. Rigidity of thoracic and abdominal muscles following fast injection of large doses of fentanyl has been described by several teams (DOBKIN et al 1964, CORSSEN et al 1965& FOLDES et d. 1966). The resistance to ventilation is caused by expiratory spas'm of the respiratory muscles.…”
Section: Fentanylmentioning
confidence: 92%
See 2 more Smart Citations
“…1) is a sedative-tranquilizer drug of the butyrophenone family, also synthesized by Janssen. Pharmacologic studies'" 5,13,20 have indicated that it has adrenergic blocking properties, antiemetic effects, and can cause hypotension, respiratory depression, and extrapyramidal reactions. Studies of fentanyl-droperidol combinations by Yelnosky and Gardockj19 have shown that droperidol, which has no analgesic effects when given alone, potentiates the analgesic actions of fentanyl in mice.…”
mentioning
confidence: 99%